If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7a + 8) = 0 Reorder the terms: 3(8 + 7a) = 0 (8 * 3 + 7a * 3) = 0 (24 + 21a) = 0 Solving 24 + 21a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 21a = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 21a = 0 + -24 21a = 0 + -24 Combine like terms: 0 + -24 = -24 21a = -24 Divide each side by '21'. a = -1.142857143 Simplifying a = -1.142857143
| a=9/4(h-24) | | 5n^2-16n+3=0 | | -266=-19r | | 2(2x-6)=-7x+10 | | x-.1x=13.50 | | 5y=15/4+25 | | -3=x-13 | | 8x+(2x+5)= | | -1.8/12.6=-6/n | | -8x-6=-78 | | 3(3x-1)+5(5x+1)=3*(3x-1)*(5x+1) | | 7/15=n/15 | | 11x-3=5x+9 | | -3=a/8 | | -20m=120 | | 7(x-8)= | | 8x^2=x+7 | | -x*45/y*95 | | -8-n=-15 | | (3t^2-t-4)(2t^2+3t-1)=6t^4+7t^3-14t^2-11t+4 | | 4-6x=-50 | | 8k+5=k-2 | | -7+p=-25 | | 6b-8=4-6b | | 3x^2=10x+25 | | 20=x/4 | | -16=-1+n | | -9z/5-2/5=-3/2+8z+6 | | 6(x-9)=5(x-5) | | -8=x/17 | | (8y^2-4y+2)-(5y^2-3y+7)= | | -12k=60 |